Adsorption of Chlorophenol from Aqueous Solution on Fluted and Commercial Activated Carbon - Ekpete, O. A.; Horsfall, M.; Tarawou, T. (Journal of Nepal Chemical Society, 2012)
The adsorption of chlorophenol by an agro-based activated carbon prepared from fluted pumpkin stem waste was investigated to assess its possible use as adsorbent. The effect of pH, initial adsorbate concentration, adsorbent dosage and contact time were studied to identify adsorption capacity of the fluted activated carbon (FAC). The results were compared to a commercial activated carbon (CAC). Adsorption data were modelled with the Langmuir, Elovich and Dubinin-Radushkevich classical adsorption isotherms. The data fitted the Elovich isotherm model better than Langmuir and Dubinin-Radushkevich. According to the evaluation using Elovich equation showed the sorption capacity obtained for chlorophenol on fluted activated carbon as 47.62 mg/g and chlorophenol for commercial activated carbon as 38.46 mg/g. The data showed that fluted activated carbon derived from fluted pumpkin stem waste, an environmental nuisance in Nigeria could be converted to a useful activated carbon for chlorophenol removal in aqueous solution. DOI: http://dx.doi.org/10.3126/jncs.v27i1.6435 J. Nepal Chem. Soc., vol. 27, 2011 p.1-10 Uploaded date: 16 July, 2012